Formação docente para a implementação da Lei 10.639/03: concepções em curso na rede municipal de São Paulo - Silva, Silmara Cardoso De Lima [UNIFESP] (2019)
This research analyzes the conceptions related to ethnic and racial issues in the continuous education process in the Municipal Education System of São Paulo. The law 10.639/03 is considered a watershed. It has changed the Law of Directives and Bases of National Education (Law 9.394/96), adding in the official educational curriculum the legal enforcement of the theme Afro-Brazilian History and Culture. We consider as valid the concept of race as a social, political and cultural construction, vital to understand the historic process of development and maintenance of inequality (GUIMARÃES, 2002; MUNANGA & GOMES, 2006; GOMES, 2012a; SCHWARCZ, 2012). We use as central concepts: the myth of racial democracy, “social whitening” and racism (considering as different conceptions: individual, institutional and structural) based in the creations of the following authors: Almeida (2018), Azevedo (2004), Domingues (2004, 2005, 2008a, 2008b), Gonzalez (1982), Moura (1983, 1988), Nascimento (1978) and Schwarcz (2012). We highlight the National Curricular Guidelines for Afro-Brazilian and African History and Culture Teaching as an official document that regulates the application of Law 10.639/03. It is simultaneously presented as a material for teacher and other education professionals training. For researching in the Municipal Education System of São Paulo, we undertake two main actions: to analyze official documents published by the Education department (SME in Portuguese) about ethnic and racial issues; personal interviews with educators involved in the continuous education process for the Law 10.639/03 implementation, such as training teachers of the Ethnic and Racial Hub of SME. Documents and interviews with critical approaches to “social whitening” and to racial democracy speech emerged, expressing the racism in the Brazilian society and posing challenges to the school institution related to ethnic and racial relations. Across the statements, it was possible to identify different conceptions between teacher and network managers, among the last ones it is clear the more conservative position.